Pemberdayaan Kader Sebaya dalam Pencegahan Tuberkulosis pada Masyarakat di Kelurahan Oesapa Kecamatan Kelapa Lima Kota Kupang Tahun 2024 - Ni Made Susilawati; Meliance Bria; Melania Fernanda Bessie (ARDHI : Jurnal Pengabdian Dalam Negri, 2025)
Tuberculosis (TB) is one of the ten diseases that most frequently causes death worldwide. This disease is caused by Mycobacterium tuberculosis and lasts a long time. Indonesia ranks third in the world in terms of the number of people suffering from tuberculosis, behind India, China and India. In East Nusa Tenggara, the most cases of tuberculosis are found in Kupang City, and Oesapa Village is one of the places where cases are still quite high. With so many TB cases still occurring, public knowledge about the symptoms, transmission and treatment of the disease is still lacking. It is hoped that empowering teenagers as health drivers will increase public awareness, especially teenagers, about prevention, symptom monitoring, and discovery and treatment of tuberculosis. Tuberculosis education can help teenagers understand the importance of maintaining a clean and healthy lifestyle to reduce TB transmission (1). This community service activity aims to increase youth knowledge and attitudes about pulmonary TB through comprehensive counseling, structured information, and youth empowerment. They also monitor communities for TB symptoms, especially children(2) The results of the activity show that the level of understanding among teenagers about TB disease has increased from 35 percent to 85 percent. There were no TB symptoms at the monitoring stage in the community, especially teenagers, and everyone was in good health. It is hoped that peer cadres (adolescents) can adopt a clean and healthy lifestyle and become pioneers in monitoring the symptoms of tuberculosis in the community to make it easier to find, handle and treat. Peer cadres can transfer information about pulmonary TB to the community, especially teenagers, by implementing Clean and Healthy Living Behavior